A first look at childhood abuse in women with obstructive sleep apnea - Pal, Amrita; Martinez, Fernando; Wagman, Jennifer; Aysola, Ravi S.; Shechter, Ari; Mysliwiec, Vincent; Martin, Jennifer L.; Macey, Paul M. (Frontiers in Sleep, 2024)
Study objectives Women who experienced childhood sexual abuse have higher rates of obesity, a risk factor for obstructive sleep apnea (OSA). We assessed if prior childhood sexual abuse was more common in women with OSA vs. those in the control group, with possible mediation by obesity. Methods In a secondary analysis of a larger project, we studied 21 women with OSA (age mean ± SD 59 ± 12 years, body mass index [BMI] 33 ± 8 kg/m2, respiratory event index [REI] 25 ± 16 events/hour, and Epworth Sleepiness Scale [ESS] score 8 ± 5) and 21 women without OSA (age 53 ± 9 years, BMI 25 ± 5 kg/m2, REI [in 7/21 women] 1 ± 1 events/hour, and ESS score, 5 ± 3). We evaluated four categories of trauma (general, physical, emotional, and sexual abuse) with the Early Trauma Inventory Self-Report–Short Form (ETISR-SF). We assessed group differences in trauma scores with independent samples t-tests and multiple regressions. Parametric Sobel tests were used to model BMI as a mediator for individual trauma scores predicting OSA in women. Results Early childhood sexual abuse reported on the ETISR-SF was 2.4 times more common in women with vs. without OSA (p = 0.02 for group difference). Other trauma scores were not significantly different between women with and without OSA. However, BMI was a significant mediator (p = 0.02) in predicting OSA in women who experienced childhood physical abuse. Conclusion Childhood sexual abuse was more common in women with vs. without OSA. BMI was a mediator for OSA of childhood physical but not sexual abuse. This preliminary hypothesis-generating study suggests that there may be physiological impacts of childhood trauma in women that predispose them to OSA.